Polydopamine-assisted decoration of ZnO nanorods with Ag nanoparticles : an improved photoelectrochemical anode - Yang, Liping (2014)
The modification of zinc oxide (ZnO) with silver (Ag) has proven to be an effective strategy to enhance the optical and electrical properties, in which the interactions between ZnO and Ag are critically determined by the structure and morphology of the ZnO–Ag hybrids. In order to achieve homogeneous and controllable distribution, polydopamine (PDA) was introduced via in situpolymerization to assist the decoration of ZnO nanorods (NRs) with Ag nanoparticles (NPs). Compared with pristine ZnO NRs, the light absorption is significantly enhanced for the PDA assisted Ag-decorated ZnO, which is attributed to the Ag NPs as well as the carbonized PDA thin film. Ag NPs of small size enhance the multiple/high-angle scattering from localized plasmonic effect, which increases the light path length hence traps more light. The carbonized PDA film is further beneficial to the absorption of the visible light. The Ag-decorated ZnO NRs on fluorine-doped tin oxide (FTO) coated glasses were then used as photoanodes of the photoelectrochemical (PEC) cell. The short circuit current density (JSC, 1.8 mA cm−2), maximum photo current conversion efficiency (PCE, 3.9%) and lifetime (3.07 mA cm−2 at 500 seconds) are achieved with an optimized loading of Ag nanoparticles derived from 0.01 M silver nitrate (AgNO3), which are found to be much higher than those of pristine ZnO NRs and other reported Ag–ZnO-based photoanodes. The overall PEC performance improvement is attributed to the localized plasmonic effect enhanced light harvesting as well as the facilitated charge transport and inhibition of recombination of electrons and holes from both Ag nanoparticles that act as an electron acceptor and carbonized PDA film as stabilizer and separator.